PEMETAAN PEMANFAATAN MEDIA AUGMENTED REALITY PADA PENDIDIKAN KEJURUAN DI DIY MENGGUNAKAN K-MEANS - Galeh Nur Indriatno Putra Pratama; Moch. Bruri Triyono; Nur Hasanah; Muhamad A. Ramadhan (LPPM Universitas Negeri Jakarta, 2022)
The purpose of this study is to reveal group data on the use of augmented reality media in teaching and learning activities so that it is easier to improve student learning outcomes. Augmented reality media was chosen based on the complexity of the scope of teaching materials consisting of thinking skills and limited practice during the implementation of distance learning. The approach for grouping the use of augmented reality media is through the K-Means algorithm with R software. The sample of this study was 136 students of Building Information and Modeling Design skills competency from 5 State Vocational High Schools spread across districts and cities, DIY Province. The review aspect used as the basis for grouping is the need for alternative media in augmented reality, ease of use, supporting facilities, and speed of understanding the material. The grouping results explain that as many as 80 students can master the material well through augmented reality media, and it is appropriate to use it during distance learning. In comparison, the remaining 56 students still find it difficult. Through the results of this grouping, it can be used to combine other media for students who still find it difficult when participating in distance learning